Catalytic performances of copper and lead (2-guanidino-benzimidazoliume) complexes in polybutadiene (PB) and hydroxyl-terminated PB epoxidation. (November 2015) - Nikje, Mir Mohammad Alavi; Soleimani, Majid; Aliakbari, Sadegh; Hajifathali, Hasan
Polybutadiene (PB) and hydroxyl-terminated PB were epoxidized using in situ-generated dimethyl dioxirane as an oxidant in the attendance of different concentrations of copper and lead (2-guanidinobenzimidazoliume) (GBH) complexes as the catalyst at 25°C. The potential of cis, trans, and vinyl double bonds toward epoxidation was considered in detail at various reaction times. The products were characterized using proton nuclear magnetic resonance and Fourier transform infrared spectroscopy techniques and data revealed that the formation of desired products were obtained without any side reaction. The results indicated the performance of calculated 0.252 mmol of GBH complexes in obtaining maximum epoxidation yield as well as selectivity in the epoxidation of cis double bonds in comparison with trans and vinyl ones.